2016
DOI: 10.4172/2155-9821.1000271
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Three Autochthonous Bacillus subtilis Strains Induce Early Appearance of Gastric Glands and Vestiges of Pylorus in Piaractus mesopotamicus Larvae

Abstract: Autochthonous microorganisms as probiotics are a novel alternative to antibiotics. The genus Bacillus is highly used by its ability to survive on adverse conditions. Piaractus mesopotamicus, a native fish, is the most produced specie in Argentinian aquaculture. The low level of knowledge, high stress conditions and demand of animals led to a deficit in the number of larvae and fry. The aim of this study was to evaluate the probiotic effect of previously selected autochthonous Bacillus on biometrical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In opposition to our findings, AZIMIRAD et al (2016) reported significant increments in both, total microorganisms and LAB counts, accompanied by significant increments in weight gain when administering Pediococcus acidilactici and fructooligo saccharide to angelfish (Pterophyllum scalare). Increment in the number of sporulated microorganisms after its administration to aquatic animals was previously described by our group (GUIDOLI et al, 2016a). Also, JAMALI et al (2015) andCHAI et al (2016) demonstrated that shrimps administered with higher doses of Bacillus strains presented higher counts of sporulated microorganisms in their guts.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…In opposition to our findings, AZIMIRAD et al (2016) reported significant increments in both, total microorganisms and LAB counts, accompanied by significant increments in weight gain when administering Pediococcus acidilactici and fructooligo saccharide to angelfish (Pterophyllum scalare). Increment in the number of sporulated microorganisms after its administration to aquatic animals was previously described by our group (GUIDOLI et al, 2016a). Also, JAMALI et al (2015) andCHAI et al (2016) demonstrated that shrimps administered with higher doses of Bacillus strains presented higher counts of sporulated microorganisms in their guts.…”
Section: Resultssupporting
confidence: 62%
“…Bacterial strains were isolated from Piaractus mesopotamicus, selected by their in-vitro expression of beneficial properties, genetically identified, registered in culture collections, tested in vivo individually and protected by patent aims (CONICET & UNNE, 2013;GUIDOLI et al, 2015GUIDOLI et al, , 2016aGUIDOLI et al, and 2016b. Lactic acid bacteria (LAB) and Bacillus cells were grown at 37°C in LAPTg (1% yeast extract, 1.5% peptone, 1% tryptone, 1% glucose, 0.1% Tween 80; pH 7.2) and Nutrient Broth (Britania © ), respectively.…”
Section: Facilities Animals and Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations